1987
DOI: 10.1037/h0080000
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness testimony research: Current knowledge and emergent controversies.

Abstract: Psychological research on eyewitness testimony has flourished over the last decade and there are now a number of findings that appear relevant to police and courts. We review some of the major eyewitness research findings regarding such things as the relationship between accuracy and confidence, the identification of perpetrators from lineups, and the influence of misleading information on eyewitness memory and reports. Next, we discuss a controversy over the application of eyewitness research in the courtroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…If, under some circumstances, witnesses' memories may differ from the actual events,jurors should be made aware ofthis. Several good discussions on this subject and other related social issues already exist (see, e.g., Ceci & Bruck, 1993;Lindsay & Read, 1994;Loftus, 1991;Wells & Turtle, 1987). Preparation of this manuscript was supported by Grant NOOOI4-95-1-0223 from the Office ofNaval Research, Grant IROI MH52808-01 from the National Institutes of Mental Health, and AFOSR Grant F49620-97-1-0054.…”
mentioning
confidence: 97%
“…If, under some circumstances, witnesses' memories may differ from the actual events,jurors should be made aware ofthis. Several good discussions on this subject and other related social issues already exist (see, e.g., Ceci & Bruck, 1993;Lindsay & Read, 1994;Loftus, 1991;Wells & Turtle, 1987). Preparation of this manuscript was supported by Grant NOOOI4-95-1-0223 from the Office ofNaval Research, Grant IROI MH52808-01 from the National Institutes of Mental Health, and AFOSR Grant F49620-97-1-0054.…”
mentioning
confidence: 97%
“…It would seem that the acceptance by jurors that there is a strong positive relationship between eyewitness accuracy and confidence is unjustified (e.g., Weingardt, Leonesio and Loftus, 1994), with some researchers suggesting that there is almost no relationship (e.g., Clifford and Hollin, 1981;Clifford and Scott, 1978;Deffenbacher, Brown and Sturgill, 1978;Leippe, Wells and Ostrom, 1978;Smith, Kassin and Ellsworth, 1989;Wells et al, 1981). Numerous studies, however, have found reliable positive correlations between accuracy and confidence (e.g., Murray and Wells, 1982;Sporer, 1992;Yarmey, 1993), and Wells and Turtle (1987) pointed out that even non-significant correlations are almost always positive. The most appropriate conclusion from a meta-analysis across 35 studies would seem to be that confidence and accuracy are modestly related, at least for identification (Bothwell, Deffenbacher and Brigham, 1987), a conclusion supported by the metaanalysis reported by Sporer, Penrod, Read and Cutler (1995).…”
mentioning
confidence: 99%
“…Finally, it is possible that, for some subjects, the "screwdriver" information could have changed the earlier memory of hammer. In a review of these reasons, Wells and Turtle (1987) state that it "remains unclear whether subjects' memories are actually altered by misleading [information] or whether their reports are altered while their memories remain intact and unaltered" (p. 373). Later, they argue that "although there seems little doubt that misleading postevent information distorts the testimony of many respondents, it is not clear if it actually alters the respondents' original memories" (p. 374).…”
mentioning
confidence: 99%